Emotional conditions and social skills in children with speech delay - Ulfa, Shahira; Hatta, Kusmawati; Nashriyah, Nashriyah (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
This study aimed to determine the emotional factors and social skills that affect a child's speech delay. Speech delay is a problem related to the speech delay of a child compared to the speech stages of his peers.This research used a qualitative descriptive research type through the Single Subject Research (SSR) method. Qualitative descriptive is a method that provides an overview and interprets the meaning of the data collected through giving attention and recording as many aspects of the situation as possible during the research to obtain a general and comprehensive description of the actual conditions. In the aspect of the emotional condition, based on the observations, it was clear that a child with speech delay had difficulty in understanding the instructions. He/she did not really understand the instructions even with short and simple sentences. He did not understand the role of objects and the names of the days of the week. His/her logical ability to reason was deemed not so developed which made it difficult to understand the causal relationship between circumstances, failing to find a solution to solve a problem. He/she also did not understand abstract theories, such as antonyms and anonymous. All of this will ultimately have a negative impact on the child's social skills.Keywords: Emotional condition, social skills, child speech delay.